2012
DOI: 10.1007/s00401-011-0938-4
|View full text |Cite
|
Sign up to set email alerts
|

Presence of an oligodendroglioma-like component in newly diagnosed glioblastoma identifies a pathogenetically heterogeneous subgroup and lacks prognostic value: central pathology review of the EORTC_26981/NCIC_CE.3 trial

Abstract: Presence of an oligodendroglioma-like component in newly diagnosed glioblastoma identifies a pathogenetically heterogeneous subgroup and lacks prognostic value: central pathology review of the EORTC 2 6981/N CIC_CE.3trialHegi, M E; Janzer, R C; Lambiv, W L; Gorlia, T; Kouwenhoven, M C M; Hartmann, C;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
63
2
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(70 citation statements)
references
References 40 publications
4
63
2
1
Order By: Relevance
“…In GB-O cases, the frequency of LOH 1p was from 12 to 24%, 19q was from 32 to 43%, and combined 1p/19q was from 22 to 28% [39,40]. In the more recent EORTC/NCIC trial study concerning a large group of 360 GB cases, an oligodendroglial component was found in 15% of all cases but co-deletion of 1p/19q was found in only one case [41]. Intriguingly, a more detailed study in GB-O using microdissection of tumor tissues with astrocytic and oligodendroglial components revealed no difference in the pattern of genetic alterations on chromosomes 1p and 19q in the same tumors [21].…”
Section: Discussionmentioning
confidence: 96%
“…In GB-O cases, the frequency of LOH 1p was from 12 to 24%, 19q was from 32 to 43%, and combined 1p/19q was from 22 to 28% [39,40]. In the more recent EORTC/NCIC trial study concerning a large group of 360 GB cases, an oligodendroglial component was found in 15% of all cases but co-deletion of 1p/19q was found in only one case [41]. Intriguingly, a more detailed study in GB-O using microdissection of tumor tissues with astrocytic and oligodendroglial components revealed no difference in the pattern of genetic alterations on chromosomes 1p and 19q in the same tumors [21].…”
Section: Discussionmentioning
confidence: 96%
“…Tumors caused by a mutation in the IDH gene encompass a spectrum from astrocytomas to oligodendrogliomas (41). At the same time, there is increasing evidence that a morphologic subclassification of gliomas lacks clinical or prognostic relevance (42), and there is growing support for an approach combining morphologic assessment and molecular profiling of gliomas (31).…”
Section: Discussionmentioning
confidence: 99%
“…16 Furthermore, a recent study reported that glioblastomas carrying IDH1 mutations are associated with a better survival than anaplastic astrocytomas without these mutations. 17 Whether the recognition of an oligodendroglial component in glioblastomas has prognostic value is still under debate [18][19][20] and also within this glioblastoma subtype a different origin of this oligodendroglial component is hypothesized. 19 An age-dependent correlation-which was found for the prognostic effect of molecular markers like TP53, 1p loss and CDKN2A-may well contribute to the inconsistencies between studies on the prognostic relevance of specific molecular markers.…”
mentioning
confidence: 99%